2018
DOI: 10.1111/jora.12400
|View full text |Cite
|
Sign up to set email alerts
|

How Does Juvenile Offending Relate to Mothers' Aspirations and Expectations for Their Sons?

Abstract: Mothers of 317 first-time juvenile offenders (M = 15.35 years old) were interviewed over 2.5 years about their expectations and aspirations for their sons' futures. Mothers' expectations were lower than their aspirations, reflecting a discrepancy between what mothers felt was important for their child's future and what they considered likely to happen. As their children continued to engage in delinquent acts, mothers' expectations for their sons' future success diminished. Youth age moderated the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…These findings have several implications. Prior work has demonstrated that involvement in the justice system, particularly for the first time, can be a stressful and negative experience for both youth and their parents (Cavanagh & Cauffman, 2017a, 2017b; Cavanagh et al, 2019). It appears that a common general response to this stress is actually to relax parental supervision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have several implications. Prior work has demonstrated that involvement in the justice system, particularly for the first time, can be a stressful and negative experience for both youth and their parents (Cavanagh & Cauffman, 2017a, 2017b; Cavanagh et al, 2019). It appears that a common general response to this stress is actually to relax parental supervision.…”
Section: Discussionmentioning
confidence: 99%
“…While some parents may have some awareness of how the system works and what responsibilities their youth have while under supervision, many parents have limited experience or knowledge of how to navigate the system (e.g., Cleary & Warner, 2017; Cleveland & Quas, 2018; Woolard et al, 2008). For instance, parents of juvenile probationers typically report limited understanding of the juvenile justice system (Cavanagh & Cauffman, 2017b) and often experience shame or feel undermined as a parent once their youth is arrested and enters the system (see Cavanagh et al, 2019). Furthermore, the financial costs may have significant repercussions for the family that both create financial strain and damage the parent–adolescent relationship.…”
Section: Parents As Partnersmentioning
confidence: 99%
“…RNR tools often assess factors such as social bonds (e.g., relationships with adult authorities; delinquent peers), labeling (e.g., expulsion from school; prior adjudication), and impulsivity because evidence suggests that these factors, among others, may affect youths’ likelihood of recidivating. Simultaneously, these same factors may affect youths’ self-perceptions and expectations about the future (e.g., Cavanagh et al, 2019; Jackson et al, 2022; Mahler et al, 2017; Testa et al, 2022). Yet, there is a dearth of evidence about whether and to what extent risk factors explain why youth do or do not feel confident about their success on probation and beyond.…”
Section: Juvenile Probationmentioning
confidence: 99%
“…Both the behaviors of caregivers and their relationship with their adolescent children can substantially influence developmental trajectories during adolescence, including participation in illegal behavior (Fix et al, 2021). Caregiver expectations about youth can affect youth behavior and have the capacity to directly and indirectly shape youth outcomes on probation (Cavanagh et al, 2019). Researchers have paid particular attention to parental monitoring, which can include monitoring by caregivers or legal guardians (Sampson & Laub, 1993).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%